Emisi dan potensi pemanasan global gas N2O hasil degradasi serasah mangrove di Pesisir Kabupaten Muna Barat - Rahman Rahman; Yusli Wardiatno; Fredinan Yulianda; Frijona Fabiola Lokollo; Iman Rusmana (Jurnal Ilmu Kehutanan, 2023)
Comprehensive research was conducted in the mangrove ecosystem of West Muna Regency to investigate the absorption of greenhouse gas (GHG) and degradation of its litter-produced GHG emissions, including N2O and carbon. The ecosystem consisted of four stations, namely Mangrove Maginti (station I), Mangrove Tiworo Tengah (station II), Mangrove Tiworo Islands (station III), and Mangrove Sawerigadi (Station IV). The research aimed to determine emissions and global warming potential (GWP) of N2O gas resulting from the degradation of mangrove litter. The team used a syringe mounted on the hood to collect gas samples and gas chromatography for concentration analysis. The correlation of emissions to environmental variables was analyzed using the Pearson correlation method. The results showed that all species' most significant and smallest average emissions were at stations III and II, with values of 0.0019 mg/m2/hour and 0.0015 mg/m2/hour, respectively. Water temperature showed a weak relationship with N2O emissions, namely r = 0.3511 (p <0.05), while water salinity did not strongly correlate with N2O emissions (r=-0.4471; p<0.05). The average GWP value ranged from 0.3665–0.6314 CO2e mg/m2/hour. Species R. apiculata and B. cylindrica at stations III and II had the largest and smallest GWP values of 0.8392 and 0.1912 CO2e mg/m2/hour, respectively.